PELAKSANAAN PENILAIAN HASIL PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SDIT TAHFIZHIL QUR’ANPELAKSANAAN PENILAIAN HASIL PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SDIT TAHFIZHIL QUR’AN - Raya Marcela; Hasimah Harahap; Muhammad Fiqri Alwi; Suyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to explore the implementation of physical education learning outcomes assessment from an affective, cognitive and psychomotor perspective at SDIT Tahfizhil Qur'an. This research uses a qualitative method with a descriptive approach. The subjects of this research were PJOK teachers at SDIT Tahfizhil Qur'an. Data collection techniques used include observation, interviews and documentation. Data validity is maintained by triangulation. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The research results show that the assessment of physical education learning outcomes in the affective aspect is adjusted to the character and abilities of each student. Assessment in the cognitive aspect is based on understanding students' knowledge, while assessment in the psychomotor aspect focuses on the skills possessed by students.